IMPLEMENTASI SISTEM INFORMASI NOTULEN RAPAT MENGGUNAKAN METODE FIFO STUDI KASUS: PERUMDAM TIRTA BENGKAYANG - Listra Firgia; Azriel Christian Nurcahyo (Informasi Interaktif, 2021)
The use of a website based application system has become an administrative requirement for employees of Perumdam Tirta Bengkayang, West Kalimantan. Meetings that are held four times a month are the obligation of employees of Perumdam Tirta Bengkayang to evaluate the performance with the director to advance Perumdam Tirta Bengkayang for the people of Bengkayang district. The purpose of this study is to implement a website-based meeting minutes application system using the FIFO (First In First Out) method. The FIFO (First In First Out) method is a method for managing and manipulating meeting data, where the first data entered will be processed first. The meeting minutes application is presented to make it easier for employees to archive data online, so that every data can be accessed when connected to the internet. By using the CodeIgniter framework, it is able to produce a system that can be understood by the employees of Perumdam Tirta Bengkayang for the implementation of their work and this system has the ability to run on computers and smartphones so that the employees of Perumdam Tirta Bengkayang can access wherever they are. The final results of this study indicate that the meeting minutes system is beneficial for Perumdam Tirta Bengkayang and has been tested by several IT experts using black box and getting 100% valid status and 119.866 ms delay testing in the very good category for using the meeting minutes application. Keywords: Meeting Minutes Application, Black Box, CodeIgnitor, FIFO.